2017
DOI: 10.1080/20426445.2016.1261528
|View full text |Cite
|
Sign up to set email alerts
|

Among-family variations of solid wood properties in 4-year-old Eucalyptus camaldulensis trees selected for pulpwood production in Thailand

Abstract: Solid wood properties were examined in eight half-sib families of 4-year-old Eucalyptus camaldulensis trees selected for pulpwood production in Thailand. The effects of radial growth rate on solid wood properties were also discussed. The mean values of green moisture content (MC) and basic density (BD) at 1.2 m heights in each family ranged from 86.3 to 106.6% and from 0.49 to 0.57 g cm −3 , respectively. Significant among-family differences were found in MC, BD and maximum height of interlocked grain (IG). Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…In addition, the basic density values obtained this study were compared with those from younger E. camaldulensis trees (Table 4). The mean basic density ranged from 0.61 to 0.73 g/cm 3 in five different clones of 5-year-old E. camaldulensis and from 0.48 to 0.55 g/cm 3 in eight half-sib families of 4-year-old E. camaldulensis trees Family (open pollinated) Nakhon Ratchasima, Thailand 4 6.5-9.3 0.48-0.55 Ishiguri et al (2017) Note: D, stem diameter at 1.3 m above the ground; BD, basic density; ND, no data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the basic density values obtained this study were compared with those from younger E. camaldulensis trees (Table 4). The mean basic density ranged from 0.61 to 0.73 g/cm 3 in five different clones of 5-year-old E. camaldulensis and from 0.48 to 0.55 g/cm 3 in eight half-sib families of 4-year-old E. camaldulensis trees Family (open pollinated) Nakhon Ratchasima, Thailand 4 6.5-9.3 0.48-0.55 Ishiguri et al (2017) Note: D, stem diameter at 1.3 m above the ground; BD, basic density; ND, no data.…”
Section: Discussionmentioning
confidence: 99%
“…planted in Thailand (Veenin et al 2005;Ishiguri et al 2017; Table 4). The results of the present study are similar to those reported by Veenin et al (2005), and the values are generally higher than those reported by Ishiguri et al (2017). Therefore, it seems that prolonged rotation age and subsequent thinning do not always lead E. camaldulensis T5 clones to produce low-quality wood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, the availability of solid wood has been considered for many fast-growing species, including Eucalyptus species (Iwasaki et al, 2012). In a previous study, we evaluated the wood properties of 4-year-old E. camaldulensis half-sib families selected based on their superior growth characteristics (Ishiguri et al, 2013(Ishiguri et al, , 2017. Significant among-family variances were identified in the stem diameter, Young's modulus of logs, moisture content, basic density, and maximum height of the interlocked grain (Ishiguri et al, 2013(Ishiguri et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%